Le capacità relazionali degli educatori nel lavoro con le famiglie. Problematiche emergenti con genitori di figli disabili - Fratini, Tommaso (Rivista Italiana di Educazione Familiare, 2020)
The article describes some educators’ ways of working with families based on relational capacities, aimed at integrating educational work with parents, specifically those with children with disabilities. Starting from a review of the psychoanalytic concept of projective identification, in particular according to the revision by Wilfred Bion, who emphasized its primitive value of communication, a model of intervention with the parents of disabled children is proposed which emphasizes the role of the transfer of projective identifications and the potential transformative value of the educator’s relational capacity. Ultimately, it emerges how much pain is denied in many families with disabled children and how important it is to translate it into words and communicate it, so that one can think about it and progressively process and overcome it. This type of psychic work is a valid complement to the more general educational work of parenting: a job that aims in the direction of the formation of a responsible and aware parenting.